Kemampuan Menulis Teks Eksposisi Melalui Pendekatan Pembelajaran Berbasis Masalah di SMP Negeri 2 Gunungsari - Muhammad Hamdi; Mahsun Mahsun; Muhammad Sukri (Jurnal Ilmiah Telaah, 2023)
This study aims to describe the ability to write expository texts through a problem-based learning approach at SMP Negeri 2 Gunungsari. This type of research is descriptive research by describing existing learning activities especially related to the problem-based learning process in students' ability to write exposition texts. In this descriptive analysis, it is described about analyzing and designing problem-based learning, implementing the learning process along with learning outcomes in the form of students' ability to write exposition texts. From the results of research and analysis of data on writing exposition texts, it was found that the aspect of writing content in writing exposition texts was still at a moderate level, which was quite evident from 13 students having scores between 17-21, aspects of student organization assessed with CK (good enough), vocabulary aspects with scores between 14-17 was obtained by 10 students with CK scores or good enough, aspects of students' use of language on fairly good abilities (CB) and mechanical aspects had a range of values from 2-5. As many as 15 students scored a very good perfect mechanical aspect (SBS) from the writing they had made. The assessment of the ability to write expository texts is based on five aspects assessment guidelines that have been prepared. Each consists of a range of values with the designation of very good perfect (SBS), pretty good (CB), moderate enough (SC), and very poor (SK). This mention certainly has several indicators that must be achieved.